Women Entrepreneurs in Rural Sindh: Issues and Challenges - Jamali, Mehwish; Siyal, Afroze; AhmedKhoso, Rafique (International Journal of Psychosocial Rehabilitation, 2020)
Rural women constitute the family that prompts society and country. General improvement of women is vital for the improvement of society and country. The research is useful for understand the different challenges and issues in self-employment, as women facing more challenges with comparison to men as they faced the people, can convince their parents, society not restrict them they established their business.The research investigates the issues and challenges faced by women enttrepreneurs in rural Sindh. The objective of research was to explore the problems which are being faced by women entrepreneurs. Data were collected from 353 women by using quantitative method. The quantitative research conducted with questionnaire of 4 independent variables and one dependent variable with 26 items on 5 point likert scale. The simple random sampling technique used for sampling the population of disitrictShaheedBenazirabad and survey filled from the 353 respondents with varying marital status, education, and age. The response rate of this study was 88.25%. Outcome from all hypothesizes reveals that all the independent variables positively influence the women entrepreneur. All the four independent variables have positive relationship with the dependant variable of women entrepreneur, whereas, issues of educational and skills has the higher relationship as compared to other independent variables. The findings also present sustainability to all the hypothesis, particularly hypothesis H1 to H4 interprets increased effect on women entrepreneur’s problems, when women entrepreneurs understand that hypothesis H3 also shows more increase in issues of education and skills with positive significant relationship and problem of resources is being insignificant in regression analysis. Results also revealed that generally all the independent variable has positive relationship with women entrepreneurs. By concluding the results, it has been observed that independent variables; family and social problem, issues of education and skills, problem of resources and problem of capital have impact on the women entrepreneurs of rural areas of Sindh.